Sustainability of The Tanjung Lesung Tourist Destination - Indrajaya, Sonny (Universitas Mercu Buana, 2024)
Tourism contributes large foreign exchange to tourism organizing countries. Tourism also creates jobs, provides income and quality to society. The Tanjung Lesung natural tourist area is part of Banten Province which has excellent natural beauty on par with Bali and Raja Ampat Papua. The potential natural beauty of the Tanjung Lesung area can be relied upon as a source of regional income. The Tanjung Lesung tourist area has many beach tourism objects, sand tourism, water tourism, underwater tourism, beautiful panoramas, unspoiled forests, tempting culinary delights, fruit native to Banten Province. The Tanjung Lesung tourist area also experienced problems after the tsunami disaster. So this is a challenge for Tanjung Lesung Tourism to provide tourist satisfaction and sustainability. The results of this research show a positive influence between variables, thus showing that tourists are satisfied with the improvement of the Tanjung Lesung tourist area after the tsunami disaster and give hope for tourism sustainability.